388 The Preschoolers Activity Trial (PAT): a Randomized Controlled Trial of Physical Activity Intervention in the Early Years. (October 2012) - Goldfield, GS; Harvey, A; Grattan, K; Colley, R; Alberga, AS; Ferraro, ZM; Temple, VA; Naylor, PJ; Barrowman, N; Adamo, KB
Abstract : Background: Physical activity (PA) provides widespread health benefits, including pediatric obesity prevention, but less than 10% of Canadian children meet PA guidelines and one in three are overweight or obese. Since PA levels track from childhood into adulthood, early intervention may increase the likelihood of a physically active lifestyle and associated health benefits throughout the lifespan. Aim: To evaluate the efficacy of an intervention with day care providers on volume and intensity of PA, motor skill development, and body mass index (BMI) in 3–5 year old children attending daycares. Methods: A randomized controlled trial comparing children (n=40) whose daycare providers received intervention designed to promote PA versus children (n=43) whose providers implemented the normal preschool curriculum. Intervention included two, 3-hour workshops plus 12 bi-monthly "booster" sessions. Children were assessed at baseline and 3-months, with a plan to collect data at 6-months. PA was measured objectively using accelerometry. Motor skills were measured using the Test of Gross Motor Development-2. BMI was assessed by measured heights and weights (kg/metres 2 ). Results: Compared to controls, the intervention produced greater increases in mean steps/day (–83 vs. +1, 185, p<0.01), gross motor percentile scores (+6 vs. +16, p<0.05) and reductions in BMI (+0.21 vs –0.22, p<0.001) at 3-months but not moderate to vigorous PA (MVPA). Conclusions: Intervening with daycare providers may be an efficacious method of increasing preschoolers' volume of PA, promoting motor skill development that is critical to PA and sport participation later in life, and reducing adiposity.